Which Aspects of Social Support Enhance Positive Mental Health in the Context of Intimate Partner Violence? - Pir, Setayesh (Violence against women, 2023)
While there is evidence that social support can mitigate mental illness symptoms associated with intimate partner violence (IPV), there is a need to explore if social support can promote positive mental health. In this New Zealand (NZ) population-based study of women who had experienced physical and/or sexual violence (n = 453), structural equation modeling (SEM) showed that most facets of social support (friends, family, and neighbors) had a significant correlation with each dimension of positive mental health, as measured by Keyes’ Mental Health Continuum Short Form (MHC-SF). Safety from IPV (no recent IPV experience) is a prerequisite before social support can assist women to attain positive mental health. Further work is required to ensure friends, family, and communities have the knowledge and resources to provide effective social support.